Odpowiedź :
Odpowiedź:
a) 0.4 + 0.25x = -2
0.25x = -2 - 0.4
0.25x = -2.4
x = -2.4 / 0.25
x = -2.4 * 4
x = -9.6
b) x - 5 = 1/3x + 1 /*3 (wszystko razy 3)
3x - 15 = x + 3
3x - x = 3 + 15
2x = 18
x = 9
c) (4x + 7)/2 - (5x - 1)/6 = x + 5 /*6
3(4x + 7) - (5x - 1) = 6x + 30
12x + 21 - 5x + 1 = 6x + 30
x = 30 - 21 - 1
x = 8
d) 4[tex]x^{2}[/tex] - 2x = (2x + 1)(2x - 3)
4[tex]x^{2}[/tex] - 2x = 4[tex]x^{2}[/tex] - 6x + 2x - 3
4[tex]x^{2}[/tex] - 4[tex]x^{2}[/tex] - 2x + 6x - 2x = -3
2x = -3
x = -3/2
Szczegółowe wyjaśnienie:
a) 0,4+0,25x= -2
0,25x=-2-0,4
0,25x= -2,4 | :0,25
x= -9,6
b) x-5=⅓x+1
x-⅓x=1+5
⅔x=6 | :⅔
x= 9
reszta w załącznikach